UNSTEADY CONVECTIVE COUETTE FLOW WITH HEAT SINK AND RADIATION EFFECTS - OMOKHUALE, EMMANUEL; Jabaka, M. L. (FUDMA JOURNAL OF SCIENCES, 2022)
In this research, the effects of heat sink and radiation on unsteady hydromagnetic convective Couette flow of a viscous, electrically conducting and incompressible fluid is studied. The governing equations that describe the flow formation, heat and mass transfer are modeled as Partial Differential Equations (PDEs) and solved numerically using Finite Element Method (FEM). The effect of physical parameters embedded on the velocity, temperature and concentration were studied graphically. It is noticed that, the momentum boundary layer increases as the value of radiation parameter is increased while the velocity of the fluid falls for higher values of the heat sink parameter